Control de inventarios y su incidencia en la gestión financiera del Instituto Ecuatoriano de Seguridad Social cantón Guaranda, provincia Bolívar, año 2019 - Garófalo García, Doris María (2020)
Inventory control is an important factor in the development of each of the activities carried out either in public or private companies, so that a bad administration can become a component capable of generating inconsistencies in the registration and management that It is given to inventories within the institution. This research study is focused on inventory control and its impact on the financial management of the Provincial Directorate of the Ecuadorian Institute of Social Security, has the main objective of improving the control and registration of inventories to facilitate the administration of stocks It also allows greater agility in the processes and activities performed by the department of existence. Within the methodology used we have the quantitative, qualitative and field, this because we went to the institution to collect the information through the interview applied to the chief financial officer and observation sheet to it regarding the control of inventories The survey applied to personnel working in the institution allowed the collection of real data and information that facilitated obtaining the results clearly and precisely for an in-depth analysis where the results obtained are 83.9% that do not have an inventory control. For this reason, the permanent inventory control system is proposed and recommended under the Weighted Average method, to improve the registration and control of inventories in accordance with what is established in current regulations regarding the control of inventories of supplies and materials, in this way To contribute to the improvement of the results of the financial management of the institution in an organized and efficient way. Keywords: inventory control, financial management, efficient, registration, stocks